Secular trend in prevalence and socioeconomic correlates of diabetes in pregnancy in Taiwan. Issue 2 (22nd November 2022) - Lu, Chin‐Li; Wu, Jia‐Ling; Li, Hung‐Yuan; Martini, Santi; Li, Chung‐Yi
Abstract: Objective: To assess the trend in prevalence and socioeconomic correlates of diabetes in pregnancy (DIP) in Taiwan from 2007 to 2014. Methods: In all, 1 606 344 pregnancies, including 199 383 DIP (1693 with pre‐pregnancy type 1 diabetes [T1DM], 17 171 with pre‐pregnancy type 2 diabetes [T2DM], and 180 519 with gestational diabetes mellitus [GDM]) were investigated. Logistic regression models were performed to identify the covariates significantly associating with DIP. Results: Over the study period, the prevalence of pre‐pregnancy T2DM increased by 568.44%; the prevalence of T1DM and GDM also increased but with a smaller magnitude. However, only the prevalence of pre‐pregnancy T2DM showed an increase after socioeconomic variables were considered. Compared with immigrant mothers, native‐born mothers had a significantly higher adjusted odds ratio of DIP, particularly pre‐pregnancy T1DM (3.33, 95% confidence interval 1.57–7.05). Additionally, indigenous mothers and those from rural areas had a higher prevalence of pre‐pregnancy T2DM but lower prevalence of GDM. Lower maternal education and income were associated with higher prevalence of pre‐pregnancy T1DM but lower prevalence of pre‐pregnancy T2DM and GDM. Conclusion: Socioeconomic variables largely accounted for the increased secular trend in pre‐pregnancy T1DM and GDM, but the prevalence of pre‐pregnancy T2DM still doubled, which was independent of socioeconomic covariates. Synopsis: Diabetes in pregnancy, particularly pre‐pregnancy type 2 diabetes, has been increasing in Taiwan, and it shows obvious socioeconomic inequality and urban–rural disparity.